Electromyographic diagnosis of ischaemic lesion of muscles of the extremities - Gayko, Oksana; Dolgopolov, Olexey; Strafun, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article deals with results of an electromyographic examination of 29 patients with ischaemic contracture of hand and 17 ones with that of foot at reactive-restorative and residual periods. Specific electromyographic changes were revealed, three clinical-electromyographic variants of ischaemic damage of extremity muscles were isolated.